2002
DOI: 10.1016/s0092-8674(02)00611-6
|View full text |Cite
|
Sign up to set email alerts
|

Hrs Regulates Endosome Membrane Invagination and Tyrosine Kinase Receptor Signaling in Drosophila

Abstract: Signaling through tyrosine kinase receptors (TKRs) is thought to be modulated by receptor-mediated endocytosis and degradation of the receptor in the lysosome. However, factors that regulate endosomal sorting of TKRs are largely unknown. Here, we demonstrate that Hrs (Hepatocyte growth factor-regulated tyrosine kinase substrate) is one such factor. Electron microscopy studies of hrs mutant larvae reveal an impairment in endosome membrane invagination and formation of multivesicular bodies (MVBs). hrs mutant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
448
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(495 citation statements)
references
References 53 publications
44
448
2
1
Order By: Relevance
“…As described above, and consistent with previous work [66], TR-avidin showed a very high degree of colocalization with LTG in the terminal lysosomal network after a 2 h chase in wild-type garland cells (Figure 5(c,d)). In Rab2 Δ1 , Vps39 Δ1 /Df, lt 11 /Df and Gie e00336 /Df cells, however, no lysosomal network was apparent, and spherical compartments strongly labeled with LTG filled the cytoplasm (Figure 5(c); Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As described above, and consistent with previous work [66], TR-avidin showed a very high degree of colocalization with LTG in the terminal lysosomal network after a 2 h chase in wild-type garland cells (Figure 5(c,d)). In Rab2 Δ1 , Vps39 Δ1 /Df, lt 11 /Df and Gie e00336 /Df cells, however, no lysosomal network was apparent, and spherical compartments strongly labeled with LTG filled the cytoplasm (Figure 5(c); Fig.…”
Section: Resultssupporting
confidence: 92%
“…Within 40 min of endocytosis, the tracer is delivered to an acidic, LTG-positive lysosomal compartment [66]. We pulsed garland cells from wild-type control and Rab2 Δ1 animals for 3 min with Texas Red-avidin (TR-avidin), followed by a 2-h chase.…”
Section: Resultsmentioning
confidence: 99%
“…The role of hrs in endosomal recycling is not inconsistent with a hypothesis suggesting that hrs or Vps27p functions in endocytic protein sorting (Katzmann et al, 2001;Bilodeau et al, 2002;Lloyd et al, 2002) and in early endosome fusion (Sun et al, 2003). These studies have suggested that hrs/Vps27p is linked with proteins required for the ubiquitination and sorting of cargo (Katzmann et al, 2001;Bilodeau et al, 2002) and that hrs inhibits homotypic early endosome fusion (Sun et al, 2003).…”
Section: Discussionmentioning
confidence: 87%
“…Hrs has homologues in insects (Lloyd et al, 2002) and fungi (Raymond et al, 1992). Deletion or mutation of hrs results in an enlarged endosomal phenotype in mouse (Komada and Soriano, 1999), fly (Lloyd et al, 2002), and yeast (Raymond et al, 1992).…”
mentioning
confidence: 99%
“…Depletion of Hrs or STAM using RNA interference (RNAi) or gene disruption inhibits RTK down-regulation in mammalian cells (Bache et al, 2003b;Hammond et al, 2003;Kanazawa et al, 2003;Lu et al, 2003) and in Drosophila (Lloyd et al, 2002). The budding yeast Saccharomyces cerevisiae also has orthologues of Hrs and STAM, which are Vps27 (vacuolar protein sorting 27) and Hse1 (Hbp/STAM/EAST 1), respectively.…”
Section: Introductionmentioning
confidence: 99%